2020
DOI: 10.1111/1440-1681.13382
|View full text |Cite
|
Sign up to set email alerts
|

ELABELA improves endothelial cell function via the ELA–APJ axis by activating the PI3K/Akt signalling pathway in HUVECs and EA.hy926 cells

Abstract: Destruction of endothelial cells (ECs) function is involved in the structural and functional pathophysiological processes of preeclampsia (PE). Vascular endothelial injury may pre‐exist for several years in women that develop PE and may pose increased risks for hypertension, coronary artery disease, and type‐2 diabetes mellitus. Previous findings showed that Elabela (ELA), the endogenous ligand of the apelin (APJ) receptor expressed mainly on ECs, may play a protective role in early pregnancy and prevent PE. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…The study performed on the population of human umbilical vein endothelial cells revealed that the treatment with ELA solutions improved their viability, migration, and tube formation abilities, which may be beneficial for the patients with features of PE. Those effects were said to be invoked by the upregulation of the APJ expression and the activation of PI3K/Akt pathways [234]. Interestingly it was noted that elabela blood levels, mRNA, and protein expressions in placental tissue are also decreased in patients with late-onset PE [235].…”
Section: Preeclampsiamentioning
confidence: 99%
“…The study performed on the population of human umbilical vein endothelial cells revealed that the treatment with ELA solutions improved their viability, migration, and tube formation abilities, which may be beneficial for the patients with features of PE. Those effects were said to be invoked by the upregulation of the APJ expression and the activation of PI3K/Akt pathways [234]. Interestingly it was noted that elabela blood levels, mRNA, and protein expressions in placental tissue are also decreased in patients with late-onset PE [235].…”
Section: Preeclampsiamentioning
confidence: 99%
“…Previous studies have reported that ELA could promote angiogenesis in HUVECs, placental development, and cardiovascular diseases. 11,13,25 Herein, we discovered for the first time that early ELA treatment promoted retinal vascular development in vivo, and our result indicated that ELA could rescue retinal vessel loss by reducing the avascular area, increasing the vascular density, and stimulating the growth of tip cells in phase 1 of OIR. In addition, ELA seems to slightly promote the development of retinal vessels in normal mice.…”
Section: Discussionmentioning
confidence: 75%
“…In cell‐based studies, Wang et al have reported that Elabela‐32 significantly improved cell viability, migration, and tube formation ability of human umbilical vein endothelial cell (HUVEC) lines and EA. hy926 cells via the activation of PI3K/AKT signaling (Wang et al 2020). Elabela‐32 treatment of mesenchymal stem cells in a hypoxic/ischemic (H/I) induced rat model demonstrated the improvement of overall cell viability via reduced mitochondrial damage, anti‐apoptosis via enhanced BCL2/BAX expression, and decreased Caspase 3 activity via the PI3K/AKT and MAPK1/3 pathways (Fu et al 2020) (Fig.…”
Section: Resultsmentioning
confidence: 99%